2012
DOI: 10.1007/s10072-012-1147-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microhemorrhage in Marchiafava–Bignami disease detected by susceptibility-weighted imaging

Abstract: Marchiafava-Bignami disease (MBD) is a rare alcohol-associated disorder. Clinical features include not only disturbed consciousness, dysarthria, tetraparesis, astasia-abasia, and symptoms of interhemispheric disconnection as initial symptoms but also cognitive deficits as clinical outcomes. The clinical significance of cerebral microhemorrhage (CMH) has been recognized in patients with cognitive deficits; however, the presence of CMH in patients with MBD has not been emphasized. The aim of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…A key application of SWI is aiding the diagnosis of diseases involving cerebral vascular pathology. These changes include, for example, vascular malformations (e.g., arteriovenous malformations and cerebral cavernous malformations), restrictions in blood flow (e.g., developmental venous anomaly) and hemorrhages (caused by e.g., cerebral amyloid angiopathy, stroke, and traumatic injuries) (1,3,(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). In these cases, a common source of contrast is oxygenation-related susceptibility changes occurring in blood products (3).…”
Section: Swi Of Cerebral Vascular Pathologymentioning
confidence: 99%
“…A key application of SWI is aiding the diagnosis of diseases involving cerebral vascular pathology. These changes include, for example, vascular malformations (e.g., arteriovenous malformations and cerebral cavernous malformations), restrictions in blood flow (e.g., developmental venous anomaly) and hemorrhages (caused by e.g., cerebral amyloid angiopathy, stroke, and traumatic injuries) (1,3,(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). In these cases, a common source of contrast is oxygenation-related susceptibility changes occurring in blood products (3).…”
Section: Swi Of Cerebral Vascular Pathologymentioning
confidence: 99%
“…MBD is most frequently seen in middle-aged or elderly chronic alcoholic males [6-9,11]. MBD was first reported in 1903 by Marchiafava and Bignami, who originally described the symptoms in Italian men with increased consumption of inexpensively manufactured Chianti red wine [1].…”
Section: Discussionmentioning
confidence: 99%
“…In a report of an MR spectroscopic study, it was suggested that inflammatory reactions accompanying demyelination and micronecrosis and secondary axonal damage might occur in the acute stage of MBD [19]. Presence of cerebral microhemorrhage on susceptibility-weighted imaging was reportedly associated with cognitive dysfunction in MBD patients, and cytotoxic edema on DWI and the ADC map might predict poor outcome [8,11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the acute phase, reduced diffusion is often seen on diffusion-weighted imaging. Contrast enhancement can be occasionally seen in the acute phase, and sometimes slight haemorrhage can also occur inside the lesion 23. Less frequently, other brain structures including white matter tracts, cerebral cortex and middle cerebellar peduncles may be involved in MBD.…”
Section: Metabolic Diseasesmentioning
confidence: 99%